Synthesis and characterization of electrospun-cellulose fibre/graphene oxide for organophosphorus pesticides adsorption study using microextraction approach - Aris, Nor Izzati Fikrah (2019)
Electrospun cellulose nanofiber/graphene oxide (CNF/GO) was synthesized, characterized and successfully utilized in solid phase membrane tip adsorption (SPMTA) as an adsorbent towards a simultaneous analysis of polar organophosphorus pesticides (OPPs) in several food and water samples prior to ultra performance liquid chromatography coupled with ultraviolet (UPLC-UV) analysis. The electrospun CNF/GO was characterized using Fourier transform- infrared spectroscopy (FTIR), BET surface area and field emission scanning electron microscopy (FESEM). Four OPPs as model analytes were selected, namely methyl parathion, ethoprophos, sulfotepp and chlorpyrifos. Several important parameters, such as sample pH, adsorption time, adsorbent dosage and initial concentration were optimized. The electrospun CNF/GO-SPMTA method showed a good linearity in between 0.05 and 10 mg/L under the optimum adsorption conditions (sample pH 12; 5 mg of adsorbent dosage; 15 min of adsorption time) with excellent correlation coefficients (R2 = 0.994 to 0.999). Acceptable RSDs for intra day (0.06 to 5.44%, n = 3) and inter day (0.17 to 7.76%, n = 3), low limits of detection (0.01 to 0.05 mg/L) and satisfactory consistency in adsorption (71.14 to 99.95%) were obtained. The adsorption data was well followed the second order kinetic model and fits the Freundlich adsorption model. A possible mechanism is by exchanging or sharing of electrons between the OPPs molecules and the vacant active sites of the electrospun CNF/GO. Therefore, the developed method showed a good acceptance to the samples and the newly synthesized electrospun CNF/GO showed a great adsorbent potential for OPPs analysis and can be used as an alternative adsorbent to be utilized in environmental applications.